Finite element analysis of polyethylene wear in total hip replacement: A literature review. (November 2019) - Wang, Lin; Isaac, Graham; Wilcox, Ruth; Jones, Alison; Thompson, Jonathan
Evaluation and prediction of wear play a key role in product design and material selection of total hip replacements, because wear debris is one of the main causes of loosening and failure. Multifactorial clinical or laboratory studies are high cost and require unfeasible timeframes for implant development. Simulation using finite element methods is an efficient and inexpensive alternative to predict wear and pre-screen various parameters. This article presents a comprehensive literature review of the state-of-the-art finite element modelling techniques that have been applied to evaluate wear in polyethylene hip replacement components. A number of knowledge gaps are identified including the need to develop appropriate wear coefficients and the analysis of daily living activities.